The metaphorical meanings of hóng ‘Red’ and bái ‘White’ in Chinese / Zheng Jie - Zheng, Jie (2015)
Color is inhered in every aspect of human life and the perception of color is regarded as one of our most fundamental cognitive abilities. A color term may be used actively for conceptualizing subjective experiences and denoting abstract concepts. In this regard, a color metaphor comes into being. In recent years, research on color metaphors has gradually been enhanced in China. There have been studies on basic color terms metaphors, non-basic color terms metaphors, specific one color metaphors from various perspectives. This dissertation seeks to analyze and specify the metaphorical meanings of two frequently used color terms hóng ‘red’ and bái ‘white’ in Chinese by using conceptual metaphor, in order to see how this the thoery based on English language can explain Chinese examples. By studying the collected data from dictionaries and a newspaper, first, the author identifies the senses of the color term hóng ‘red’ and bái ‘white’ into two kinds: the literal meaning and the metaphorical meaning. It is found that the literal meaning of hóng and bái is the color ‘red’ and ‘white’, respectively. In this case, both color terms are applied to denote the physical color of various objects in the world. On the other hand, the metaphorical meanings refer to the subjective experiences or abstract concepts associated with these two color terms. Second, through cognitive analysis, major conceptual metaphors for both color terms hóng ‘red’ and bái ‘white’ are put forward. Third, through further examination of the meaning extensions of these two color terms, the author has discovered that metonymy is applied to structure and understand the abstract domains, which play an essential role in the metaphorical projection of color terms. That is to say, metaphor is based on metonymy. Metonymy and metaphor are a correlated system during the process of these two color terms’ meaning extension. This dissertation is a tentative study of color metaphors in Chinese. It reinforces and develops some theories of the contemporary cognitive approach to metaphor, providing a more scientific picture of color terms. Key Words: color term, red, white, cognitive linguistics, conceptual metaphor, conceptual metonymy.